Clinical and prognostic relationships of pulmonary artery to aorta diameter ratio in patients with heart failure: a cardiac magnetic resonance imaging study. Issue 1 (23rd January 2018) - Pellicori, Pierpaolo; Urbinati, Alessia; Zhang, Jufen; Joseph, Anil C.; Costanzo, Pierluigi; Lukaschuk, Elena; Capucci, Alessandro; Cleland, John G.F.; Clark, Andrew L.
Abstract : Background: The pulmonary artery (PA) distends as pressure increases. Hypothesis: The ratio of PA to aortic (Ao) diameter may be an indicator of pulmonary hypertension and consequently carry prognostic information in patients with chronic heart failure (HF). Methods: Patients with chronic HF and control subjects undergoing cardiac magnetic resonance imaging were evaluated. The main PA diameter and the transverse axial Ao diameter at the level of bifurcation of the main PA were measured. The maximum diameter of both vessels was measured throughout the cardiac cycle and the PA/Ao ratio was calculated. Results: A total of 384 patients (mean age, 69 years; mean left ventricular ejection fraction, 40%; median NT‐proBNP, 1010 ng/L [interquartile range, 448–2262 ng/L]) and 38 controls were included. Controls and patients with chronic HF had similar maximum Ao and PA diameters and PA/Ao ratio. During a median follow‐up of 1759 days (interquartile range, 998–2269 days), 181 patients with HF were hospitalized for HF or died. Neither PA diameter nor PA/Ao ratio predicted outcome in univariable analysis. In a multivariable model, only age and NT‐proBNP were independent predictors of adverse events. Conclusions: The PA/Ao ratio is not a useful method to stratify prognosis in patients with HF.